The influence of grazing and cultivation on runoff, soil erosion, and soil nutrient export in the central highlands of Ethiopia - Adimassu, Zenebe; Tamene, Lulseged D.; Degefie, Degefie T. (Springer, 2020)
Background: Grazing by livestock and cultivation have been considered as two important causes of soil erosion and nutrient export. However, there has been limited evidence that grazing or cultivation matters to soil erosion and nutrient export in Ethiopia. Hence, this study was conducted in the Galesa watershed in Ethiopia to examine the effects of grazing and cultivation on runoff, soil loss, and nutrient export. Daily values of runoff, soil erosion, and nutrient outflow were measured for three consecutive years following standard procedures. Independent t test was performed to check if the means of runoff, soil loss, and nutrient loss from grazing and cultivated lands were significantly different. Moreover, repeated analysis of variance (ANOVA) was used to test if mean values of runoff, soil loss, and nutrient export varied significantly over the study years.